Scaffolding Case Studies: Advancing Competency-Based Nurse Practitioner Education. - Ainslie, Marcy; Hebert, Danielle; Miller, Joseph; Griffith, Patricia B.; Moore, Jeanne; Luke, Sheba; Venzke, Margaret Hadro (Nurse Educator)
Background: Nursing education is transitioning to competency-based education (CBE). A key principle of CBE is scaffolding curricula from simple to complex to facilitate student learning. Problem: There is no standardized method of scaffolding nurse practitioner (NP) curricula. Approach: A workgroup of NP educators analyzed visit types—such as wellness, acute, chronic, and transition of care visits—to determine the appropriate placement of case scenarios for early, middle, or late-stage learners. Each case was then aligned with the educational preparation requirements for specific NP populations to identify which populations would benefit most from the scenario. Outcomes: A structured classification system, using predefined criteria, was developed to scaffold case scenarios in NP education. This systematic arrangement supports the implementation of CBE and facilitates learning. Conclusions: The scaffolding model can be used with a variety of learning resources and provides a standardized method for scaling complexity within NP curricula.